Analisis Perangkat Pembelajaran Matematika Berbasis Open-Ended yang Berorientasi Higher Order Thinking Skills Ditinjau dari Aspek Validitas - Wulandari, Enika; Ayda, Erni (Edumatica : Jurnal Pendidikan Matematika, 2021)
The problem in this research is that the validity aspect of open-ended-based mathematics learning tools that is oriented towards Higher Order Thinking Skills (HOTS) in quadratic equation material is unknown. The purpose of this study was to determine the validity aspects of open-ended-based mathematics learning tools oriented to HOTS quadratic equation material for class IX. This research includes content analysis research. The subject of the research is an open-ended-based mathematics learning tool that is oriented to HOTS on the quadratic equation material for class IX including the Learning Implementation Plan (RPP), Student Worksheet (LKPD) and open questions that measure HOTS. The data were taken by three validators using the RPP validity questionnaire, LKPD validity questionnaire, question validity questionnaire and the advice documentation sheet from the validator. Data were analyzed descriptively and converted in a qualitative scale. The results showed that the validity of the open-ended RPP based on the HOTS orientation was in the very good category, the validity of the open-ended LKPD based on the HOTS orientation was in the very good category, the validity of the open-ended which measured HOTS was in the very good category. Based on these results, it can be concluded that the open-ended-based mathematics learning tool oriented to Higher Order Thinking Skills (HOTS) on quadratic equation material has very good validity.